Blutiger Strand is not just a war movie. - Bowman, Pete 1957- (Explosive Media, 2020)
"American Marines storm ashore on a Japanese-held island and push inland while their enemy plans a counter attack, in this look at warfare. Fighting men on both sides are haunted by memories of home and the horrifying, sickening images they experience in combat."--Container
Bildformat 1.85:1 (16:9)
Keywords: United States / Marine Corps / Drama; USA -- Marine Corps; World War, 1939-1945 / Japan; Combat / Personal narratives / Drama; Weltkrieg (1939-1945); Kriegsfilm; Zweiter Weltkrieg; USA; Japan; Film; DVD-Video